A Strange Cartography: Leylines, Landscape and “Deep Mapping” in the Works of Alfred Watkins - James Thurgill (Humanities, 2015)
In 1921 the photographer, antiquarian and amateur archaeologist Alfred Watkins, delivered his newly formed thesis on the origins of ancient alignments in the west of England to the Woolhope Naturalists’ Field Club of Hereford. Watkins posited a correlation between ancient forts, moats, mounds, churches, trees and place names, which he had shown to produce straight lines running across the landscape. In 1922 Watkins published his first book on the subject, Early British Trackways, mixing amateur archaeology, social history and supposition to introduce what Watkins named “leylines” and setting out the guidelines for other would-be ley hunters. This paper explores Watkins’ ley hunting as a practice of “deep mapping”, examining its use as an applied spatial engagement with the hidden trajectories of the landscape. In addition to providing a concise cultural history of the leyline, with particular reference to the works of Alfred Watkins, this paper develops a critical engagement with ley-walking through an auto-ethnographic response to a leyline that has been mapped and walked in Norfolk, England.